Preparation method and application of biomass charcoal / PDMS composite material with piezoelectric property

By synergizing the three-dimensional body structure biomass carbon aerogel with PDMS prepolymer solution, the piezoelectric performance of biomass carbon/PDMS composite materials is improved, and the performance of existing biomass porous carbon materials and ceramic piezoelectric materials is solved. The problem of insufficient results has achieved high compression and excellent mechanical properties, and is suitable for smart wearable devices and flexible electronic devices.

CN119307102APending Publication Date: 2025-01-14NORTH CHINA INST OF AEROSPACE ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411497790.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The weak piezoelectric effect generated by existing biomass porous carbon materials during pressure or deformation and the insufficient mechanical properties of pure ceramic piezoelectric materials limit their application in structural engineering.

Method used

By synergizing the three-dimensional body structure biomass carbon aerogel with PDMS prepolymer solution, using interface interaction and stress transfer mechanisms to improve the piezoelectric sensitivity and response speed of composite materials, biomass carbon with piezoelectric characteristics is prepared by using the following methods: /PDMS composite material.

Benefits of technology

It realizes the high compression, excellent mechanical properties and piezoelectric properties of composite materials, and is suitable for flexible electronic devices for energy conversion and storage, and is suitable for applications of smart wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307102A_ABST
    Figure CN119307102A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a biomass charcoal / PDMS composite material with piezoelectric characteristics, and the preparation method comprises the following steps: taking biomass as a raw material, carrying out gelation reaction at low temperature, and then carrying out bidirectional freezing treatment to obtain an ordered three-dimensional body structure of at least centimeter level; and carrying out freeze drying treatment on the obtained three-dimensional body structure to obtain the collagen aerogel. The collagen aerogel is subjected to high-temperature treatment in a protective atmosphere, biomass carbon aerogel is obtained, and the treatment temperature is 800-1600 DEG C; dissolving a PDMS prepolymer in an ethyl acetate solvent to form a PDMS prepolymer solution, wherein the volume ratio of the PDMS prepolymer to the ethyl acetate solvent is 1: (0.5-10); and completely immersing the obtained biomass charcoal aerogel in the PDMS prepolymer solution, dipping for 10-60 minutes, then putting into a drying oven, and carrying out curing reaction at the temperature of 50-80 DEG C, so as to finally obtain the biomass charcoal / PDMS composite material. According to the composite material, the piezoelectric sensitivity and the response speed of the composite material are improved through interface interaction and a stress transfer mechanism.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of intelligent wearable piezoelectric materials, and in particular to a method for preparing a biochar / PDMS composite material with piezoelectric properties and application of the biochar / PDMS composite material in piezoelectric drive. Background Art

[0002] Biomass carbon composites have broad application prospects in the field of smart wearable devices, but current research still faces many challenges. By optimizing the preparation process, exploring the relationship between material performance and structure, and strengthening the surface chemical properties and physical strength, the practical application of biomass carbon composites in the field of smart wearables can be effectively promoted. The porous structure and high specific surface area of ​​existing biomass porous carbon materials may cause charge separation and polarization phenomena inside the material when it is subjected to pressure or deformation, and can only produce a weak piezoelectric effect. However, current piezoelectric materials, such as pure ceramic piezoelectric materials, have poor compression and mechanical properties. When subjected to high pressure, their internal structure will be irreparably damaged, limiting their application in structural engineering. Summary of the invention

[0003] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to provide an intelligent wearable biomass carbon aerogel composite material with piezoelectric properties. The composite material adds aerogel with a three-dimensional structure as a conductive filler or a reinforcing phase into a piezoelectric polymer matrix, and improves the piezoelectric sensitivity and response speed of the composite material through interface interaction and stress transfer mechanism.

[0004] The technical solution adopted by the present invention to solve the technical problem is: In a first aspect, the present invention provides a method for preparing a biomass charcoal / PDMS composite material having piezoelectric properties, the process of the preparation method being: Step 1: using biomass as raw material, subjecting it to a gelation reaction at low temperature and then to a bidirectional freezing treatment, to obtain an ordered three-dimensional structure at least at the centimeter level; Step 2, freeze-drying the three-dimensional structure obtained in step 1 to obtain collagen aerogel; Step 3, treating the collagen aerogel at high temperature under a protective atmosphere to obtain biomass carbon aerogel, the treatment temperature being 800-1600° C.; Step 4, dissolving the PDMS prepolymer in an ethyl acetate solvent to form a PDMS prepolymer solution, wherein the volume ratio of the PDMS prepolymer to the ethyl acetate solvent is 1:0.5-10; Step 5: Completely immerse the biochar aerogel obtained in step 3 in the PDMS prepolymer solution of step 4 for 10-60 minutes. The PDMS prepolymer solution is wrapped around the outside of the biochar aerogel skeleton and partially fills the inside of the biochar aerogel skeleton through capillary and adsorption effects. Then, the biochar aerogel is placed in an oven at 50-80°C for curing reaction to finally obtain a biochar / PDMS composite material.

[0005] Furthermore, the biomass is at least one of collagen, cellulose, chitosan and silk.

[0006] Furthermore, in step 1, the temperature of the gelation reaction at low temperature is 0-5°C, and the reaction time is 10-30h; liquid nitrogen is used as a cold source to perform a bidirectional freezing treatment, and the freezing time of the bidirectional freezing treatment is 0.5-10h.

[0007] Furthermore, in step 2, the freeze-drying pressure is -0.1 MPa, and the drying time is 20-50 hours.

[0008] Furthermore, in step 3, the protective atmosphere is nitrogen. During the high-temperature treatment, the tube furnace is evacuated three times by a vacuum pump, and the temperature is gradually increased to 800-1600° C. in a step-by-step heating manner, and kept warm for 0.5-3 hours.

[0009] Furthermore, in step 4, the curing reaction time is 15-30 hours.

[0010] In a second aspect, the present invention provides a biochar / PDMS composite material with piezoelectric properties, which is obtained by the above-mentioned preparation method. The composite material is placed on a pistil without causing the pistil to deform and has compression cycle stability; the carbon content is 5-30 wt%.

[0011] In a third aspect, the present invention provides an application of the composite material, wherein the composite material is applied to a multifunctional system of flexible electronic devices for energy conversion and storage and can be used as a piezoelectric drive.

[0012] Furthermore, the composite material is used in smart wearables.

[0013] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adds aerogel made of biochar with an ordered three-dimensional structure as a conductive filler or reinforcing phase into a piezoelectric polymer matrix (PDMS (polydimethylsiloxane)), and improves the piezoelectric sensitivity and response speed of the composite material through interface interaction and stress transfer mechanism.

[0014] 2. In the present application, biomass materials (including but not limited to collagen, cellulose, chitosan, etc.) are prepared into an ordered three-dimensional structure through a bidirectional freezing process. The biochar obtained after high-temperature carbonization still has an excellent ordered porous structure. After co-assembly with the PDMS prepolymer solution polymer, the biochar and the polymer interact synergistically to effectively transmit stress and current in the entire porous skeleton. The carbon skeleton deforms under the action of stress, resulting in internal charge redistribution and producing a piezoelectric effect. The material has high compressibility, excellent mechanical properties and piezoelectric properties.

[0015] 3. It can be seen from the graph of the time-dependent response under different compressive strains of the embodiments of the present invention that the composite material has a relatively fast response and excellent compression cycle stability, making it suitable for accurately detecting various human biological and motion signals, and is expected to be applied to the multifunctional system of flexible electronic devices for energy conversion and storage, such as flexible sensors, smart wearable devices, artificial skin and other fields.

[0016] 4. The present invention sets different freeze-drying times and high-temperature treatment temperatures, and the strength and mechanical properties of the carbon skeleton are different. The preferred biomass of the present invention is used as a carbon source, which has rich oxygen-containing functional groups. After being compounded with the PDMS prepolymer solution, it will form a strong hydrogen bond interaction at the surface interface, improve the interfacial bonding strength of the composite material, optimize the interface microstructure of the composite material, and finally further improve the mechanical properties and piezoelectric properties of the material. In addition, the carbon source of the present application also has the characteristics of high economy and convenient operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a picture of the effect of the biochar / PDMS composite material in Example 1 lightly touching the pistil of a flower.

[0018] Figure 2 This is a scanning electron microscope image of the composite material of Example 1, and its carbon content is 17.24wt%.

[0019] Figure 3 The piezoelectric performance test results of the composite material of Example 1 are shown in FIG.

[0020] Figure 4 This is a scanning electron microscope image of the random biomass carbon / PDMS composite material of Comparative Example 1.

[0021] Figure 5 This is the scanning electron microscope image of the biochar / PDMS composite material of Comparative Example 2, where (a) is 1:0.2 and (b) is 1:20.

[0022] Figure 6The biomass carbon / PDMS composite material is prepared from the PDMS prepolymer solution with a concentration of 1:12 in Comparative Example 2. DETAILED DESCRIPTION

[0023] The present invention is further explained below in conjunction with the embodiments and drawings, but this is not intended to limit the scope of protection of the present application.

[0024] The preparation method of the biomass carbon / PDMS composite material with piezoelectric properties of the present invention uses biomass (collagen, cellulose, chitosan, silk, etc.) as raw materials, performs a gelation reaction at low temperature, then performs a bidirectional freezing treatment, and finally performs a freeze-drying treatment and a high-temperature carbonization treatment under a protective atmosphere to obtain a biomass carbon aerogel; The biochar aerogel is immersed in a PDMS prepolymer solution, and after drying and curing, a biochar / PDMS composite material is obtained; the PDMS prepolymer solution is obtained by dissolving a PDMS prepolymer in an ethyl acetate solvent and mixing them uniformly, and the volume ratio of the PDMS prepolymer to the ethyl acetate solvent is 1:0.5-10.

[0025] The preferred freezing time for bidirectional freezing is 0.5-5 h.

[0026] Different concentrations of PDMS prepolymer solutions in the present invention will lead to significant differences in the piezoelectric properties and mechanical properties of the biochar / PDMS composite material. PDMS prepolymer solutions with too high or too low concentrations will have different defects. When the concentration of the PDMS prepolymer solution is high, the porous structure will be filled with the PDMS prepolymer solution, which will lead to the deterioration of the piezoelectric properties of the biochar / PDMS composite material. However, a PDMS prepolymer solution with too low a concentration cannot just wrap the carbon skeleton, resulting in the exposure of the carbon skeleton, and the resulting piezoelectric current transmission efficiency is reduced, which leads to a decrease in the piezoelectric properties of the biochar / PDMS composite material. The present application obtains the optimal value of the PDMS prepolymer solution concentration through multiple experiments. The PDMS prepolymer solution at a given concentration can just completely wrap the carbon skeleton and retain a multi-layer porous structure, thereby improving the piezoelectric properties while ensuring excellent mechanical properties.

[0027] Because the performance of piezoelectric materials is closely related to their internal fillers and interface interactions, the present invention selects biochar with a high piezoelectric coefficient and good mechanical properties as a porous three-dimensional skeleton. The biochar aerogel contains more oxygen-containing functional groups, which increases the interface interaction with the polymer. It has a good effect directly on the polymer PDMS without the need for surface treatment. The interface bonding strength and charge transfer efficiency between the polymer and the carbon skeleton are significantly improved through a reasonable interface structure, thereby obtaining a biochar / polydimethylsiloxane (PDMS) composite material with an ideal microstructure and piezoelectric properties.

[0028] The material preparation process in the present invention is simple and widely available. A new piezoelectric material is generated by curing and polymerizing the biochar material and the PDMS prepolymer solution. The PDMS prepolymer solution in the present invention helps to increase the carbon content of the carbon skeleton in the composite material, and improves the mechanical properties, mechanical properties and piezoelectric properties of the biochar / PDMS composite material by increasing the carbon content of the carbon skeleton. The amount of piezoelectric particles added has a significant effect on the piezoelectric properties. Within a certain range, as the amount of piezoelectric filler added increases, the piezoelectric properties of the composite material will be improved. This is because more piezoelectric particles can more effectively convert mechanical energy into electrical energy, thereby enhancing the piezoelectric effect of the composite material. However, when the amount added exceeds a certain limit for most of the time, the piezoelectric performance of the composite material will reach an upper limit, and may even decline, because too many piezoelectric particles may cause agglomeration and uneven dispersion between particles, reducing the overall performance and piezoelectric effect of the composite material. The three-dimensional structure carbon skeleton used in the present invention can effectively avoid the agglomeration and uneven dispersion of the piezoelectric filler and the polymer compounding process, thereby effectively improving the overall piezoelectric performance of the composite material.

[0029] The biochar aerogel of the present invention has good compressive resilience itself, and works synergistically with the PDMS prepolymer solution. After curing, the composite material as a whole has better compressive resilience and piezoelectric properties, and can remain intact under large compressive strain and has excellent conductive properties.

[0030] In the present invention, a cross-linking agent can be added to the biomass raw material to keep it in a three-dimensional structure state, but the addition of the cross-linking agent cannot reduce the piezoelectric properties of the composite material. If more cross-linking agents are added to the biomass raw material, the pores in the aerogel will be larger, forming a loose and porous structure, which will lead to reduced piezoelectric properties when it is later cured with the polymer. In the present invention, the polymer can be wrapped around the skeleton to form an elastic shell, which can improve the piezoelectric properties and compressive resilience under the same conditions. Collagen aerogel presents a three-dimensional structure on a macro scale, which can be controlled above the cm level and is a complete whole.

[0031] Example 1 In this embodiment, collagen is used as a biomass raw material to prepare a biomass carbon / PDMS composite material with piezoelectric properties.

[0032] The collagen (porcine source) (col) prepared by enzymatic hydrolysis was placed in a low temperature environment (4°C) for gelation reaction for 20 h. Using the bidirectional freezing technology, the copper table was placed in a liquid nitrogen solution to fully cool it and keep the surrounding temperature stable. The gelled sample was placed on the copper table and liquid nitrogen was used as a cold source to freeze it in a directional manner. The ambient temperature gradient changed, and the farther away from the liquid nitrogen surface, the higher the temperature. The freezing time was 1 h. Subsequently, the directional gel filled with ice crystals in the pores was placed in a freeze dryer. The frozen gel was freeze-dried in a low pressure (0 MPa) environment for 30 h to finally obtain collagen aerogel.

[0033] The obtained collagen aerogel was placed in a tubular furnace, and the tubular furnace was evacuated three times by a vacuum pump while nitrogen was introduced as a protective gas. The temperature was gradually raised to 1000°C by a step-by-step heating method, and the temperature was kept for 1 hour to finally obtain the biomass carbon aerogel.

[0034] 10 ml of PDMS prepolymer (Dow Corning DC184 A component) was dissolved in 40 ml of ethyl acetate solvent, and a small amount of curing agent (Dow Corning DC184 B component) was added. The mixture was evenly mixed under mechanical stirring to obtain a PDMS prepolymer solution with a volume ratio of 1:4. The biochar aerogel was immersed in the PDMS prepolymer solution with a volume ratio of 1:4. The PDMS prepolymer solution was fully impregnated in the skeleton through capillary and adsorption effects. After the impregnation, it was placed in an oven at 60°C for curing reaction to form a fully polymerized PDMS polymer on the skeleton for 24 hours, and finally a biochar / PDMS composite material was obtained.

[0035] The composite material obtained in this example was tested for related properties: Figure 1 The composite material is placed on the flower and lightly touches the pistil. As can be seen from the figure, the pistil does not deform when the composite material is placed on it, indicating that the biochar / PDMS composite material of the present invention is light in weight and low in density, and can significantly reduce the weight of the device when used on a wearable device.

[0036] Figure 2 This is a scanning electron microscope image of the composite material, which has a carbon content of about 17.24wt%. From the image, we can see the multi-layer porous structure of the internal structure of the composite material, and the PDMS polymer wrapped on the carbon skeleton and maintained in a porous state, which can ensure the overall elastic performance.

[0037] Figure 3This is the time-dependent response of the biochar / PDMS composite material under different compression strains. It shows that the biochar / PDMS composite material can generate piezoelectric current and time responsiveness under different compression strains. It can be seen that the generated current value is high and the response time is fast. When the compression degree is 50%, the current can reach 75 mA, and the response time is 60s. When the compression degree is 20%, it responds almost immediately, and the current is about 25mA; as the compression degree increases, its piezoelectric current increases.

[0038] Example 2 In this example, collagen (porcine source) (col) prepared by enzymatic hydrolysis was placed in a low temperature environment (4°C) for gelation reaction for 10 h. Using the bidirectional freezing technology, the copper table was placed in a liquid nitrogen solution to fully cool it, and the surrounding temperature was kept stable. The gelled sample was placed on the copper table to freeze and freeze it in a directional manner for 1 h. Subsequently, the directional gel with ice crystals filled in the pores was placed in a freeze dryer, and the frozen gel was freeze-dried in a low-pressure environment for 20 h to finally obtain collagen aerogel.

[0039] The obtained collagen aerogel was placed in a tubular furnace, and the tubular furnace was evacuated three times by a vacuum pump while nitrogen was introduced as a protective gas. The temperature was gradually raised to 800 °C by a step-by-step heating method and kept for 3 h to finally obtain the biochar aerogel.

[0040] 10 ml of PDMS prepolymer was dissolved in 5 ml of ethyl acetate solvent, and the mixture was evenly mixed under mechanical stirring to obtain a PDMS prepolymer solution. The biochar aerogel was immersed in the PDMS prepolymer solution. The PDMS prepolymer solution was fully impregnated in the skeleton through capillary and adsorption effects. The final composite material was placed in an oven at 50°C for a curing reaction for 15 hours to finally obtain a biochar / PDMS composite material.

[0041] Example 3 In this example, collagen (porcine source) (col) prepared by enzymatic hydrolysis was placed in a low temperature environment (4°C) for 30 h for gelation reaction. Using the bidirectional freezing technology, the copper table was placed in a liquid nitrogen solution to fully cool it, and the surrounding temperature was kept stable. The gelled sample was placed on the copper table to freeze and freeze it in a directional manner for 10 h. Subsequently, the directional gel filled with ice crystals in the pores was placed in a freeze dryer, and the frozen gel was freeze-dried in a low-pressure environment for 50 h to finally obtain collagen aerogel.

[0042] The obtained collagen aerogel was placed in a tubular furnace, and the tubular furnace was evacuated three times by a vacuum pump while nitrogen was introduced as a protective gas. The temperature was gradually raised to 1600 °C by a step-by-step heating method, and the temperature was kept for 0.5 h to finally obtain the biochar aerogel.

[0043] 10 ml of PDMS prepolymer was dissolved in 100 ml of ethyl acetate solvent, and evenly mixed under mechanical stirring to obtain a PDMS prepolymer solution with a concentration of , and the biochar aerogel was immersed in the PDMS prepolymer solution. Through capillary and adsorption effects, the PDMS prepolymer solution was fully impregnated in the skeleton, and then placed in an oven at 80 ° C for curing reaction for 30 hours to finally obtain a biochar / PDMS composite material.

[0044] Example 4 In this example, a cellulose aqueous solution (cellulose solid content of 8 wt.%) was placed in a low temperature environment (4°C) for 25 h for gelation reaction. Using the two-way freezing technology, the copper table was placed in a liquid nitrogen solution to fully cool it and keep the ambient temperature stable. The gelled sample was placed on the copper table. By controlling the freezing time for 8 h, a structurally controllable three-dimensional system was obtained, and the three-dimensional structure was maintained. Subsequently, the frozen gel filled with ice crystals in the pores was placed in a freeze dryer, and the frozen gel was freeze-dried in a low-pressure environment of 0 MPa for 35 h to finally obtain collagen aerogel.

[0045] The obtained cellulose aerogel was placed in a tubular furnace, and the tubular furnace was evacuated three times by a vacuum pump while nitrogen was introduced as a protective gas. The temperature was gradually raised to 1000 °C by a step-by-step heating method and kept for 2 h to finally obtain the biochar aerogel.

[0046] 10 ml of PDMS prepolymer was dissolved in 80 ml of ethyl acetate solvent and mixed evenly under mechanical stirring to obtain a PDMS prepolymer solution. The biochar aerogel was immersed in the PDMS prepolymer solution. Through capillary and adsorption effects, the PDMS prepolymer solution was fully impregnated in the skeleton. Then, it was placed in an oven at 75 °C for curing reaction for 25 h to finally obtain a biochar / PDMS composite material.

[0047] The piezoelectric properties of the composite materials of the above-mentioned embodiments 2-4 are relatively poorer than those of the embodiment 1, and the resilience of different embodiments is slightly different, but as a whole, a continuous electron path can be formed in the skeleton and stable piezoelectric properties can be maintained.

[0048] The present invention can change the degree of polymerization of the polymer by adjusting the reaction conditions (such as temperature, concentration, reaction time, etc.) during the synthesis process to regulate the mechanical properties and piezoelectric properties of the material.

[0049] Comparative Example 1 Different biomasses (collagen, cellulose, chitosan or silk protein) were directly carbonized in a tube furnace. The tube furnace was evacuated three times by a vacuum pump while nitrogen was introduced as a protective gas. The temperature was gradually raised to 1000 °C and kept for 2 h by a step-by-step heating method to finally obtain biochar.

[0050] 10 ml of PDMS prepolymer was dissolved in 40 ml of ethyl acetate solvent and uniformly mixed under mechanical stirring to obtain a PDMS prepolymer solution. The biochar was dispersed in the PDMS prepolymer solution by mechanical stirring, and then placed in an oven at 75 °C for curing reaction for 25 h to obtain a random biochar / PDMS composite material.

[0051] Figure 4 This is a scanning electron microscope image of the random biochar / PDMS composite material of Comparative Example 1. It can be seen from the image that the biochar is unevenly dispersed in the polymer matrix and is easy to agglomerate, which seriously affects the mechanical properties and piezoelectric properties of the material.

[0052] Comparative Example 2 In this comparative example, the volume ratio of PDMS prepolymer to ethyl acetate solvent was changed to 1:0.2, 1:12, and 1:20 based on Example 1. Figure 5 The figure shows the SEM photos of the composite materials prepared by different volume ratios of PDMS prepolymer and ethyl acetate solvent. It can be seen from the figure that when the volume ratio of PDMS prepolymer to ethyl acetate solvent is 1:0.2, the solution viscosity is too high, the impregnation in the skeleton is not complete, there are large holes inside the biomass carbon aerogel, and a continuous electronic path cannot be formed inside the skeleton, which is easily interrupted. If the solution viscosity is too low (such as the volume ratio of PDMS prepolymer to ethyl acetate solvent is 1:20), a thin layer is formed on the skeleton, the polymer does not fill the skeleton perfectly, the pores are too large, and the piezoelectric performance stability is poor.

[0053] like Figure 6 As shown in the figure, when the volume ratio of PDMS prepolymer to ethyl acetate solvent is 1:12, the current value cannot return to the initial value after each cycle of piezoelectricity. This is because the concentration of the PDMS prepolymer solution is too low, resulting in poor rebound performance of the sample, and it cannot return to the initial state after extrusion.

[0054] Unless otherwise specified, the raw materials involved in the present invention can be obtained through commercial purchase or directly produced through existing technologies.

[0055] Any matters not described in the present invention are applicable to the prior art.

Claims

1. A method for preparing a biomass charcoal / PDMS composite material with piezoelectric properties, characterized in that: The process of the preparation method is: Step 1: using biomass as raw material, subjecting it to a gelation reaction at low temperature and then to a bidirectional freezing treatment, to obtain an ordered three-dimensional structure at least at the centimeter level; Step 2, freeze-drying the three-dimensional structure obtained in step 1 to obtain collagen aerogel; Step 3, treating the collagen aerogel at high temperature under a protective atmosphere to obtain biomass carbon aerogel, the treatment temperature being 800-1600° C.; Step 4, dissolving the PDMS prepolymer in an ethyl acetate solvent to form a PDMS prepolymer solution, wherein the volume ratio of the PDMS prepolymer to the ethyl acetate solvent is 1:0.5-10; Step 5: Completely immerse the biochar aerogel obtained in step 3 in the PDMS prepolymer solution of step 4 for 10-60 minutes. The PDMS prepolymer solution is wrapped around the outside of the biochar aerogel skeleton and partially fills the inside of the biochar aerogel skeleton through capillary and adsorption effects. Then, the biochar aerogel is placed in an oven at 50-80°C for curing reaction to finally obtain a biochar / PDMS composite material.

2. The preparation method according to claim 1, characterized in that: The biomass is at least one of collagen, cellulose, chitosan and silk.

3. The preparation method according to claim 1, characterized in that: In step 1, the temperature of the gelation reaction at low temperature is 0-5°C, and the reaction time is 10-30 hours; liquid nitrogen is used as a cold source to perform a bidirectional freezing treatment, and the freezing time of the bidirectional freezing treatment is 0.5-10 hours.

4. The preparation method according to claim 1, characterized in that: In step 2, the freeze-drying pressure is -0.1 MPa and the drying time is 20-50 hours.

5. The preparation method according to claim 1, characterized in that: In step 3, the protective atmosphere is nitrogen. During high-temperature treatment, the tube furnace is evacuated three times by a vacuum pump, and the temperature is gradually increased to 800-1600° C. by a step-by-step heating method, and kept warm for 0.5-3 hours.

6. The preparation method according to claim 1, characterized in that: In step 4, the curing reaction time is 15-30 hours.

7. A biochar / PDMS composite material with piezoelectric properties, obtained by the preparation method according to any one of claims 1 to 6, wherein the composite material is placed on a stamen without causing the stamen to deform and has compression cycle stability; the carbon content is 5-30wt%.

8. An application of the composite material according to claim 7, characterized in that: The composite material is applied to a multifunctional system of flexible electronic devices for energy conversion and storage, and can be used as a piezoelectric drive.

9. The use according to claim 8, characterized in that: The composite material is used in smart wearables.